2014
DOI: 10.1002/alr.21449
|View full text |Cite
|
Sign up to set email alerts
|

Asthma with allergic rhinitis management in China: a nationwide survey of respiratory specialists at tertiary hospitals

Abstract: PRMs in China demonstrated an up-to-date comprehension of asthma management (>90%); however, knowledge gaps existed in their concepts of AR and asthma-AR comorbidity. Thus, further education is warranted for PRMs regarding the importance of AR in asthma patients, definitive diagnosis (allergy tests), classifications of AR, and treatment guidelines for the asthma-AR comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…To be exact, a cross-sectional, hospital-based survey of 1,931 AR patients in two modernized cities (Guangzhou and Zhuhai) in Southern China and the prevalence of concomitant asthma for AR patients is 5.33% (103 of 1,931) 25. Comparatively, another cross-sectional questionnaire study surveyed the diagnostic methods and treatment patterns for asthma-AR comorbidity by primary respiratory medicine specialty (PRMs) from 98 hospitals across China and the PRMs reported an estimated prevalence of asthma-AR comorbidity of > 30% at their clinics 26. On the contrary, research conducted on 20,051 patients with asthma in an outpatient setting covering all territories of China confirmed that AR presented in 69.9% of patients with asthma,27 further suggesting the upper and lower airway relationship between AR and asthma.…”
Section: Current Status Of Comorbid Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…To be exact, a cross-sectional, hospital-based survey of 1,931 AR patients in two modernized cities (Guangzhou and Zhuhai) in Southern China and the prevalence of concomitant asthma for AR patients is 5.33% (103 of 1,931) 25. Comparatively, another cross-sectional questionnaire study surveyed the diagnostic methods and treatment patterns for asthma-AR comorbidity by primary respiratory medicine specialty (PRMs) from 98 hospitals across China and the PRMs reported an estimated prevalence of asthma-AR comorbidity of > 30% at their clinics 26. On the contrary, research conducted on 20,051 patients with asthma in an outpatient setting covering all territories of China confirmed that AR presented in 69.9% of patients with asthma,27 further suggesting the upper and lower airway relationship between AR and asthma.…”
Section: Current Status Of Comorbid Allergic Diseasesmentioning
confidence: 99%
“…For example, optimized instruments based on objective tests have been more adequately employed to assess the prevalence of AR in the past 5 years than before. Meanwhile, the definition of PRMs has been given great attention because PRMs with greater work experience and higher professional titles estimated treating a significantly higher proportion of patients with AR as well as asthma-AR comorbidity 26. Moreover, allergy specialists in China have confirmed that the incidence of pollen-, dust mites- and mold-sensitive AR can be predicted by employing models based on prevailing meteorological conditions,70 providing critical methods for the prevention of environmental exposure.…”
Section: Prospectsmentioning
confidence: 99%
“…Previously, the Asthma Insights and Managements surveys reported an underuse of ICS to treat asthma together with an overuse of oral steroids in the Asia-Pacific region compared with the US, Canada, and Europe 23. Knowledge gaps in the management of coexistent asthma-AR were also highlighted in a recent cross-sectional survey of physicians in China, in which a fifth of those surveyed reported the use of oral leukotriene antagonists as the most commonly used drug for treating AR while also controlling asthma 24…”
Section: Introductionmentioning
confidence: 99%
“…The main factor influencing treatment choice in this survey for both GPs and pediatricians was reported to be AR guidelines (in 86% of interviewed physicians) which contrasts from a survey in 1,200 primary care practitioners in Australia, Brazil, Canada, France, Germany, Italy, Spain and the UK, where only 3% of them reported to follow the AR guidelines, and 27% acknowledged that they adapted their management based on AR guidelines for individual patient treatment [4]. From a survey in China, respiratory medicine specialists had high-level knowledge of asthma management (>90%) but there were areas identified for improvement in their perception of AR and coexistent asthma [21]. Beside patient affordability, and drug availability, patient preference is an important factor influencing treatment choice.…”
Section: Discussionmentioning
confidence: 99%